Assessment of Water Quality in Billings Reservoir: Analysis of Pollution Impacts and Fish Mortality - Marcondes, Marta Angela; Souza, Camila Menezes de; Franchi, Renata Borges (Technical and Scientific Journal Green Cities, 2025)
The objective of this study is to analyze water quality in hydric bodies in the Braço do Rio Grande region, focusing on identifying parameters that influence their environmental health. The methodology included sampling at three strategic points using sterilized Falcon tubes and conducting microbiological and physicochemical analyses according to the Standard Methods for the Examination of Water and Wastewater protocols. This study addresses a theoretical gap resulting from the scarcity of data on water quality in urban reservoirs, highlighting the academic importance of this topic for environmental management. The results indicated the presence of thermotolerant bacteria and other pollution indicators, underscoring the need for interventions to preserve water quality in this region. Theoretical contributions include expanding knowledge about the health of urban hydric bodies, while methodological implications involve the use of sampling and analysis techniques that can be replicated in other studies. Socially, the study raises community awareness of the importance of preserving water resources, and environmentally, it emphasizes the urgency of actions to mitigate contamination, protect local aquatic biodiversity, and safeguard public health.
Keywords: Analysis; Contamination; Water Quality